2020
DOI: 10.3389/fgene.2020.00448
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometers Provide Early Genetic Selection Criteria for Jumping Horses

Abstract: The aim of this study was to evaluate the genetic component of the locomotor jumping ability, via a wearable accelerometer sensor, and to estimate the genetic correlation with performance in competition, to introduce such criteria in selection schema. A sample of 1,056 young 3-year-old horses were equipped with a 3-dimensional accelerometer during a free jumping test, in regular breeding shows from 2015 to 2017. Seven variables were extracted from the dorso-ventral acceleration curve for the last three jumps o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Consistent, within-horse jump techniques have been described in the longitudinal studies of Santamaria et al [20,21], who reported that many characteristics of jumping performance, including vertical velocity at takeoff, vertical displacement of the CM during the aerial phase, and aerial phase duration were strongly correlated in the same horses jumping a vertical fence at 6 months and 4 years of age. High reliability and heritability coefficients for kinematic jumping parameters have also been reported in the field of population genetics, further supporting the apparently inherent and repeatable nature of within-horse jump technique [22][23][24][25]. Thus, horses may execute fences using a consistent, individual jump technique, but the effect of different fence heights and widths on within-and between-horse variation in jump technique has yet to be investigated.…”
Section: Introductionmentioning
confidence: 81%
“…Consistent, within-horse jump techniques have been described in the longitudinal studies of Santamaria et al [20,21], who reported that many characteristics of jumping performance, including vertical velocity at takeoff, vertical displacement of the CM during the aerial phase, and aerial phase duration were strongly correlated in the same horses jumping a vertical fence at 6 months and 4 years of age. High reliability and heritability coefficients for kinematic jumping parameters have also been reported in the field of population genetics, further supporting the apparently inherent and repeatable nature of within-horse jump technique [22][23][24][25]. Thus, horses may execute fences using a consistent, individual jump technique, but the effect of different fence heights and widths on within-and between-horse variation in jump technique has yet to be investigated.…”
Section: Introductionmentioning
confidence: 81%
“…However, repeatability for the trait of "height at the withers" was on the medium level, and it was higher than that for the measured height at the withers from the biometric part of the evaluation. As reported earlier [21], measured traits and more objective traits [27,28] are less repeatable and heritable, because some of the variation may be due to judges' knowledge of the catalogue and their subjectivity [9,27,28].…”
Section: Breed and Stallion Effectmentioning
confidence: 87%
“…Horse-breeding societies use semi-objective measures to evaluate conformation and movement [15][16][17]. Objective measures are available [18][19][20][21][22], but they are often difficult to implement within equestrian events. The traditional points system has been criticized because of the lack of agreement with the information on functional performance [23].…”
Section: Introductionmentioning
confidence: 99%
“…IMUs can also be used for the evaluation of free jumping performances during regular breeding. Ricard et al [ 83 ] used an IMU sensor (Equimetrix ® ) to estimate the correlation between the genetic component of jumping ability and the jumping performance during a breeding program. Jump duration and judgement scores were heritable and genetically correlated to competition performance: 0.59 (standard error [SE]: 0.13) for jump duration and 0.60 (SE: 0.11) −0.77 (SE: 0.12) for judgement scores [ 83 ].…”
Section: Horse–rider Interaction and Imusmentioning
confidence: 99%